Poesia e Filosofia nella storia del Pensiero Spagnolo Contemporaneo: un’analisi a partire dalle esperienze emblematiche di José Ferrater Mora, José Gaos e María Zambrano - Dalla Mora, Roberto (Bollettino Filosofico, 2017)
In the contemporary Spanish philosophical thought, the question about the relationship between Poetry and Philosophy is fundamental, and the experiences of the thinkers of Spanish Generation of 1939 has been essential to define this new thematic. The historical circumstances –as the Spanish Civil War and the exile– showed them the limit of the absolute rationality, and forced them to configure a philosophical proposal where life and logical rationality could be expressed together. The aim of this paper is to underline this element of Spanish contemporary thought, throughout the analysis of the proposal of three of the most important philosophers of this period: José Ferrater Mora, José Gaos and María Zambrano. These authors practiced both activity, Poetry and Philosophy, so the study of their works is particularly recommended in order to achieve the objective of this paper.